Volatile chemical composition of essential oil from Bursera graveolens (Kunth) Triana & Planch and their fumigant and repellent activities - Beatriz Eugenia Jaramillo-Colorado; Samyr Suarez-López; Vanessa Marrugo-Santander (Acta Scientiarum. Biological Sciences, 2019)
The objectives of this work were the study of the volatile chemical composition of essential oils (EO’s) from Bursera graveolens obtained in the locality of Malagana, municipality of Mahates, Bolívar, Colombia, as well as to evaluate their repellent and fumigant properties. EO’s were extracted by hydro-distillation and characterized by gas chromatography-mass spectrometry (GC-MS). The major compounds found in B. graveolens were limonene (42.2%), pulegone (20.9%), carvone (7.5%), caryophyllene (4.1%), and trans-carveol (3.8%). The repellent activity of EO’s was determined by the area preference method, where the EO of B. graveolens presented repellent activity against the Tribolium castaneum weevil at a concentration of 1 at 2% and 4 hours of exposure (88.1 and 88.6% respectively). B. graveolens essential oil was more effective in its fumigant activity with LC50 of 108.2 μg oil mL-1. Also, the fumigant and repellent activities of two individual compounds present in the oil were evaluated, that is, limonene (majority) and caryophyllene. The results indicated that B. graveolens essential oil could be a promising alternative to new natural repellents and biocides.